Java EE 7 : the big picture - Coward, Danny (McGraw-Hill Education, 2015)
"The Definitive Guide to Java Platform, Enterprise Edition 7Java EE 7: The Big Picture uniquely explores the entire Java EE 7 platform in an all-encompassing style while examining each tier of the platform in enough detail so that you can select the right technologies for specific project needs. In this authoritative guide, Java expert Danny Coward walks you through the code, applications, and frameworks that power the platform. Take full advantage of the robust capabilities of Java EE 7, increase your productivity, and meet enterprise demands with help from this Oracle Press resource. Explore the features of the Java servlet model and Java servlet API Create dynamic web content with JavaServer Pages and JavaServer Faces Build websites for nonbrowser clients with JAX-RS Push data to web clients using Java WebSockets Secure web applications Work with web component APIs Maximize enterprise beans for multithreading, asynchronous processes, transactions, and more Access relational databases with the Java Database Connectivity APIs and the Java Persistence API Understand the packaging and deployment mechanisms of Java EE applications Work with Java EE Contexts and Dependency Injection Secure enterprise beans in a Java EE application Enable parallel processing with Java EE concurrency APIs "--